Strengthening Infection Prevention Through Organizational Integration: A Longitudinal Review Of Cross-Departmental Contributions In Healthcare Facilities (The Review of Diabetic Studies, 2025)
Infection prevention and control (IPC) continues to be a critical priority in modern healthcare settings, requiring coordinated actions that extend beyond single departments. This longitudinal review synthesizes evidence on how organizational integration among clinical, diagnostic, and supportive departments strengthens infection control outcomes over time. Findings highlight the evolving roles of nursing, laboratory services, pharmacy, environmental health, infection control units, and health information systems in reducing healthcare-associated infections (HAIs). The review identifies key determinants of success, including standardized protocols, interdepartmental communication systems, leadership support, technology-enabled surveillance, and staff education. Extracted indicators from longitudinal studies show that integrated IPC significantly improves early detection, antimicrobial stewardship, environmental safety, and patient outcomes. A conceptual framework and departmental synergy map are proposed to guide healthcare organizations toward high reliability and sustained IPC performance. This review provides actionable recommendations for enhancing organizational alignment, strengthening collaboration, and implementing system-level interventions that promote a culture of safety. The findings contribute to the development of comprehensive IPC strategies aligned with global and national healthcare transformation goals.